Gastroprotective Activity of Inhaled Curcuma Rhizome Essential Oil on Male Mice Induced by Acute Stress - Jeni Mistya Intan Awani; Jason Merari Peranginangin; Tri Wijayanti (GLOBAL HEALTH SCIENCE GROUP, 2026)
Stress is the body's response to physical, emotional, or psychological stress. One of the causes of stress is sound. This study aims to determine the gastroprotective activity of the stomach of male mice given inhalation of curcuma rhizome essential oil and induced acute stress using an ultrasonic modification method. The study was conducted experimentally using male mice divided into 6 groups, namely group 1 as a normal control that was not induced by anything. Group 2 was induced by stress with ultrasonic, group 3 was a positive control given ranitidine 0.8 mg/20 grams of mouse body weight which was given orally and induced stress with ultrasonic. Group 4 was induced by stress and given inhalation of curcuma rhizome essential oil at a concentration of 0.5%, Group 5, was induced by stress and given inhalation of curcuma rhizome essential oil at a concentration of 1% and Group 6, was induced by stress and given inhalation of curcuma rhizome essential oil at a concentration of 2%. Stress was induced using an ultrasonic method, and the parameters measured were the pH of gastric fluid. The results of the study showed that inhalation of curcuma rhizome essential oil provided a gastroprotective effect, indicated by a decrease in the number of gastric ulcers and the severity of gastric ulcers.